Edukasi Poster untuk Tingkatkan Pengetahuan Overweight Siswa di SMAN 1 Samarinda: Poster dan Overweight - Miza Almas, Raisah; Noer Wahyudi, Suryani; Aulia Juniarti, Tirsa; Shahira Nur, Nadhira; Derajat, Derajat; Wirapuspita, Ratih (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2025)
The prevalence of overweight among students of SMA Negeri 1 Samarinda is the main focus in efforts toimprove adolescent health. The main objective of this activity is to increase students' knowledge regarding the risksand impacts of being overweight. So it is hoped that it can increase motivation for change at the student level.Education is carried out using an interactive lecture method through the poster media 'Recognize and PreventOverweight'. Evaluation of effectiveness is carried out using the Wilcoxon test. The results of the study showed asignificant difference between the level of student knowledge before and after counseling, with a significance valueof 0.000 (p <0.05). This finding indicates that the use of posters as an educational medium is effective in increasingthe knowledge of students of SMA Negeri 1 Samarinda. It is hoped that this research can increase adolescentawareness of the importance of a healthy lifestyle.